Balloon pulmonary angioplasty can be an effective and safe therapeutic option in non-surgical elderly patients - Velázquez Martín, Maite; Maneiro Melón, Nicolás; Albarrán González-Trevilla, Agustín; Sarnago Cebada, Fernando; Huertas Nieto, Sergio; Cruz-Utrilla, Alejandro; Hinojosa, Williams; López-Gude, María Jesús; Alonso Charterina, Sergio; Revilla Ostolaza, Yolanda; Aguilar Colindres, Ricardo José; Arribas Ynsaurriaga, Fernando; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Advanced age, frailty, and age-related comorbidities are the major causes of pulmonary endarterectomy disqualification in patients with chronic thromboembolic pulmonary hypertension (CTEPH). Balloon pulmonary angioplasty (BPA) is an attractive and less invasive therapy for elderly patients. However, information about the safety, procedure tolerance, and effectiveness of BPA in elderly patients is limited. Objective and methods We aimed to analyze the safety, tolerance, and efficacy of BPA in CTEPH patients aged ≥70 years. This observational, descriptive, and retrospective series included consecutive patients aged ≥70 years, who underwent completed or interrupted BPA programs at a pulmonary hypertension reference center between May 2013 and May 2022. Results We enrolled 155 patients in our institution's BPA program. Among these, 33 patients were aged ≥70 years (mean age, 76.4 years; women, 75.8%) and had finished or interrupted BPA programs. In this cohort, we performed 116 BPA procedures (average, 3.6 ± 1.8 sessions/patient). Among the 33 patients, 19 (57.6%) completed treatment for all lobes, while the BPA program was interrupted in the remaining 14 (42.4%). Among all 33 patients, BPA was associated with a significant reduction in mean pulmonary arterial pressure (39.2 ± 9.3 vs. 32.8 ± 8.8 mmHg; p < 0.001) and pulmonary vascular resistance (6.7 ± 3.1 vs. 4.4 ± 2.0 WU; p < 0.001), along with an improvement in the cardiac index (2.5 ± 0.6 vs. 2.8 ± 0.7 L/min/m2; p = 0.04) with significant reductions in the N-terminal prohormone of brain natriuretic peptide level (pre-BPA, 353 pg/mL [207–1,960 pg/mL] vs. post-BPA, 167 pg/mL [73–629 pg/mL]; p = 0.03). The patients' functional class improved, and pulmonary hypertension-targeting drug requirements were significantly reduced. The pulmonary injury appeared in 3.4% of the 116 procedures, of which 50% were of grade 2. No patient of ≥70 years had grade 5 pulmonary injury. One periprocedural mortality was recorded (3%), and the median follow-up period was 2.8 years. The survival rate of the entire cohort at 1 and 3 years was 90.5 and 82.8%, respectively. Conclusion BPA is an effective and safe approach in patients aged ≥70 years. It significantly improves patients' functional class, hemodynamic, and biomarkers, and reduces their pulmonary hypertension-targeting medical therapy requirements. These successes were achieved even though a significant percentage of patients did not complete the therapy. The rates of procedural complications and periprocedural mortality were low. Survival at 1 and 3 years was good in comparison to that of younger patients undergoing BPA.